Die Bergmeister von Krupka, Berginspektoren und die Herren von Sternberg - Kilián, Jan (Theatrum historiae, 2012)
The bureaucratic apparatus of Krupka in the early Modern Age, a mining town on the foothills of the Ore Mountains, has so far attracted little or superficial attention of professional papers. This is even more true of the Baroque period, when the town was held by the Sternbergs. This paper can not contain a comprehensive presentation of the issue and remains a partial probe into the situation at the turn of the 17th and 18th century and the relations between the community, the aristocrats and their officers on the grounds of disputes in the domains of mining and municipal privileges.